2015
DOI: 10.1016/j.devcel.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

MCRS1 Binds and Couples Rheb to Amino Acid-Dependent mTORC1 Activation

Abstract: Ras homolog enriched in brain (Rheb) is critical for mechanistic target of rapamycin complex 1 (mTORC1) activation in response to growth factors and amino acids (AAs). Whereas growth factors inhibit the tuberous sclerosis complex (TSC1-TSC2), a negative Rheb regulator, the role of AAs in Rheb activation remains unknown. Here, we identify microspherule protein 1 (MCRS1) as the essential link between Rheb and mTORC1 activation. MCRS1, in an AA-dependent manner, maintains Rheb at lysosome surfaces, connecting Rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 62 publications
4
74
0
Order By: Relevance
“…A subpopulation of Rheb, which tethers to membranes through a farnesyl lipid modification, resides at the lysosome [65,126-128]. Farnesylation of Rheb provides a relatively weak membrane anchor but is essential for robust mTORC1 signaling [27].…”
Section: The Lysosome: Key Site Of Mtorc1 Regulation By Pi3k Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…A subpopulation of Rheb, which tethers to membranes through a farnesyl lipid modification, resides at the lysosome [65,126-128]. Farnesylation of Rheb provides a relatively weak membrane anchor but is essential for robust mTORC1 signaling [27].…”
Section: The Lysosome: Key Site Of Mtorc1 Regulation By Pi3k Signalingmentioning
confidence: 99%
“…Rag binding does not directly activate mTORC1 but instead serves to bring it into proximity with lysosomally localized Rheb. A major pool of the TSC complex has also been identified at the lysosome and dynamic regulation of its localization here holds the key to Rheb activation [65,75,128,129]. In the absence of growth factors, the TSC complex accumulates at the lysosome [65,75].…”
Section: The Lysosome: Key Site Of Mtorc1 Regulation By Pi3k Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has found that other cellular stresses, including a lack of amino acids, similarly promote lysosomal accumulation of TSC through a mechanism that may be partially dependent on the Rag GTPases (Demetriades et al, 2014; Demetriades et al, 2016). Interestingly, the lysosomal recruitment of the Rheb GTPase itself is also regulated by amino acids, which stimulate the binding of Rheb to microspherule protein 1 (MCRS1) (Fawal et al, 2015). The localization of Rheb-MCRS1 to the lysosome depends upon both amino acids and the presence of an active Ragulator and v-ATPase.…”
Section: Regulation Of Mtorc1 and Mtorc2 By Nutrient And Endocrine Simentioning
confidence: 99%
“…The localization of Rheb-MCRS1 to the lysosome depends upon both amino acids and the presence of an active Ragulator and v-ATPase. In addition to its localization function, MCRS regulates the association of Rheb with TSC1/2 in an amino acid dependent manner (Fawal et al, 2015). The intricate ballet by which mTORC1 and its activators are localized to the lysosome, while its inhibitors depart (Figure 3), highlights the necessity for precise coordination of upstream signals with downstream cellular responses.…”
Section: Regulation Of Mtorc1 and Mtorc2 By Nutrient And Endocrine Simentioning
confidence: 99%